Praktikum Anatomi Tumbuhan Berbantuan Mikroskop Viewer Online untuk Meningkatkan Kecerdasan Jasmaniah Kinestetik Mahasiswa - Sugianto; Ismail Fikri Natadiwijaya; Eva Yuliana; Ipin Aripin; Anilia Ratnasari; Gita Erlangga Kurniawan; Dwi Fauzi Rachman (Jurnal Penelitian Pendidikan IPA, 2023)
Initial conditions of plant anatomy practical learning at Wiralodra University indicate a lack of training in students' kinesthetic bodily intelligence. This is evident as students do not feel proficient in operating microscopes and determining microscope magnification, indicating a lack of trained kinesthetic bodily intelligence. Based on this issue, a digital microscope is needed to train students' kinesthetic bodily intelligence in plant anatomy practicals. The innovation of digital microscope technology is necessary as a supporting tool for plant anatomy practicals. The objective of this study is to develop an Online Microscope Viewer to enhance students' multiple intelligences in plant anatomy practicals. Considering the nature of the study as the development of an Online Microscope Viewer, the research design used is Research and Development. The study subjects consist of 185 second-semester biology education students from the Biology Education program at Wiralodra University, divided into five classes. The sampling method used is cluster random sampling, with two classes, Bio B (experimental group) and Bio D (control group), selected under the condition that the populations are homogeneous. The results indicate that the developed Online Microscope Viewer used in plant anatomy practicals is highly valid. The developed Online Microscope Viewer can significantly enhance students' kinesthetic bodily intelligence in plant anatomy practicals, categorized as high. There is a significant difference in the improvement of students' kinesthetic bodily intelligence between the class using the Online Microscope Viewer and the class using binocular light microscopes.